Conservation Science in Indonesia: Protecting the Endangered Species of the Archipelago - Al-Husna, Shofa; Wiriya, Mongkut; Mongga, Albertus Elinda (Indonesia Discourse, 2025)
This study explores the field of conservation science in Indonesia, focusing on the protection of endangered species across the nation’s vast archipelago. As one of the world’s most biodiverse countries, Indonesia faces immense challenges in conserving its unique flora and fauna, many of which are threatened by habitat loss, illegal poaching, and the effects of climate change. The research investigates the current conservation strategies employed in Indonesia, including efforts to establish protected areas, engage local communities, and enforce anti-poaching laws. Findings highlight the successes and limitations of these strategies, with some species seeing positive outcomes from concerted conservation efforts, while others continue to decline despite these interventions. Key challenges identified include inadequate funding, insufficient local engagement, and the ongoing conflict between development and conservation priorities. The novelty of this study lies in its comprehensive evaluation of Indonesia’s conservation landscape, considering both ecological and socio-political factors that influence conservation outcomes. Given Indonesia’s critical role in global biodiversity preservation, this research is timely and vital for informing future conservation policies and strategies. The study contributes to the broader discourse on biodiversity conservation by offering recommendations to enhance the effectiveness of conservation efforts, such as strengthening community-based initiatives, improving law enforcement, and fostering international collaboration to protect endangered species in Indonesia.